Geochemistry and related studies of Clyde Estuary sediments. (13th November 2018) - Jones, David G.; Vane, Christopher H.; Lass-Evans, Solveigh; Chenery, Simon; Lister, Bob; Cave, Mark; Gafeira, Joana; Jenkins, Gareth; Leslie, Alick; Breward, Neil; Freeborough, Katy; Harrison, Ian; et al.
ABSTRACT: Geochemical and related studies have been made of near-surface sediments from the River Clyde estuary and adjoining areas, extending from Glasgow to the N, and W as far as the Holy Loch on the W coast of Scotland, UK. Multibeam echosounder, sidescan sonar and shallow seismic data, taken with core information, indicate that a shallow layer of modern sediment, often less than a metre thick, rests on earlier glacial and post-glacial sediments. The offshore Quaternary history can be aligned with onshore sequences, with the recognition of buried drumlins, settlement of muds from quieter water, probably behind an ice dam, and later tidal delta deposits. The geochemistry of contaminants within the cores also indicates shallow contaminated sediments, often resting on pristine pre-industrial deposits at depths less than 1m. The distribution of different contaminants with depth in the sediment, such as Pb (and Pb isotopes), organics and radionuclides, allow chronologies of contamination from different sources to be suggested. Dating was also attempted using microfossils, radiocarbon and 210 Pb, but with limited success. Some of the spatial distribution of contaminants in the surface sediments can be related to grain-size variations. Contaminants are highest, both in absolute terms and in enrichment relative to the natural background, in the urban and inner estuary and in the Holy Loch, reflecting the concentration of industrial activity.